In vitro inhibition of protein glycation and advanced glycation end products formation by hydroethanolic extract and two fractions of Simaba trichilioides roots - Motta, Bruno Pereira [UNESP]; Kaga, Anderson Kiyoshi [UNESP]; Oliveira, Juliana Oriel [UNESP]; Inacio, Maiara Destro [UNESP]; da Silva, Cledson Ferreira; de Sousa Junior, Paulo Teixeira; Brunetti, Iguatemy Lourenço [UNESP]; Baviera, Amanda Martins [UNESP] (Taylor & Francis, 2018)
Long-term hyperglycemia maintenance is responsible for increased protein glycation and formation of advanced glycation end products (AGEs), both are associated with the onset of diabetes mellitus complications. Efforts have been made to discover new agents having antiglycation potential. The aim of this study was to investigate the effects of the hydroethanolic extract and the ethyl acetate and methanolic fractions of Simaba trichilioides roots on the formation of AGEs. In an in vitro model system of protein glycation, incubations with hydroethanolic extract, ethyl acetate or methanolic fractions of S. trichilioides decreased the fluorescent AGEs, and markers of tyrosine and tryptophan oxidation. Protein crosslinking was reduced in the presence of the ethyl acetate fraction of S. trichilioides. Simaba trichilioides roots seem to be a promising source of compounds having ability to prevent glycoxidation changes, with potential applications in complementary therapies for management of diabetic complications.
Keywords: antiglycation activity; diabetes mellitus; glycoxidative stress; Simaba trichilioides A St.-Hill; Simaroubaceae